Effectiveness of Combined Healthy Lifestyle Education and Yoga Therapy on Self-Reflection and Personal Insight in Overweight Adults at Risk of Type 2 Diabetes - Agahheris, Mojgan; Kordmirza Nikoozadeh, Ezzatolah; Abdolkarimy Nazary , Maryam; Saleh, Afagh (Health Nexus, 2026)
This study examined the effectiveness of a combined healthy lifestyle education and yoga therapy program in improving self-reflection and personal insight among overweight adults at risk of developing type 2 diabetes. A quasi-experimental pretest–posttest design with a follow-up assessment and a non-intervention control group was used. Forty eligible adults attending health-related services in Tehran were selected through purposive sampling and randomly allocated to an experimental group (n = 20) or a control group (n = 20). The experimental group participated in a structured 10-session weekly program integrating education on nutrition, physical activity, sleep, stress management, self-care, goal setting, and maintenance of healthy behavior with yoga postures, breathing exercises, relaxation, body awareness, mindfulness, and self-compassion practices. The control group received no intervention during the study period. Self-reflection and personal insight were measured with the Self-Reflection and Insight Scale. Data were analyzed using descriptive statistics and mixed repeated-measures analysis of variance. Significant time-by-group interactions were observed for self-reflection, personal insight, and the total score. In the experimental group, mean self-reflection increased from 39.65 at pretest to 53.40 at posttest, and mean personal insight increased from 24.80 to 34.60. These improvements remained largely stable at follow-up, whereas the control group showed no meaningful change. The interaction effect sizes were large for self-reflection (partial η² = .651), personal insight (partial η² = .616), and the total score (partial η² = .709). Pairwise comparisons confirmed significant improvements from pretest to posttest and from pretest to follow-up, with no significant decline between posttest and follow-up. The findings suggest that integrating lifestyle education with yoga-based mind–body practices may strengthen constructive self-observation and clearer understanding of health-related thoughts, emotions, and behaviors in overweight adults at elevated diabetes risk. Larger trials with active controls, longer follow-up periods, and objective metabolic outcomes are required.